Developmental Links Between Externalizing Behavior and Student–Teacher Interactions in Male Adolescents With Psychiatric Disabilities. Issue 1 (1st March 2019) - Hopman, Juliette A. B.; Tick, Nouchka T.; van der Ende, Jan; Wubbels, Theo; Verhulst, Frank C.; Maras, Athanasios; Breeman, Linda D.; van Lier, Pol A. C.
Abstract: Students exhibiting challenging externalizing behaviors may benefit from supportive interactions with teachers. However, if students show high levels of externalizing behaviors, this may negatively impact on student–teacher interactions, and vice versa. We therefore examined bidirectional developmental links between student–teacher interactions and externalizing behavior of male adolescents placed in special education because of psychiatric disabilities. Participants were 584 adolescents ( M age = 15.0 years, SD = 1.7) and their teachers from 14 Dutch special education schools. At 3 time points, student-reports of student–teacher interactions and teacher-reports of adolescents' externalizing behavior were collected. Using autoregressive cross-lagged models, results indicate that externalizing behavior predicted decreases in supportive interactions (β = −.09, p = .02), but not in negative interactions. Student–teacher interactions did not show a significant influence on externalizing behavior. Our results highlight externalizing behavior as an important target for interventions intended to improve student–teacher interactions.